The Effectiveness of Task-Based Learning in Historical and Cultural Research Method Classes - Harun, Yessy; Biduri, Febi Nur (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study analyzes the effectiveness of task-based learning in the History and Culture Research Methods class. This approach focuses on engaging students through goal-oriented assignments that are relevant to real life. This study aimed to see the effectiveness of task-based learning on students' abilities in the Historical and Cultural Research Methods class and to find an effective implementation strategy. This study used a descriptive qualitative approach to collect data through observation and research on ten Japanese Language and Culture Study Program students, semester 6, Darma Persada University, academic year 2021/2022. The research outcomes suggest that using the task-centered approach proves efficient in augmenting student involvement and active involvement in the educational process. The use of tasks that are relevant to the learning objectives increases student interest and facilitates learner-centered learning. This study underscores the importance of a task-based approach in learning Historical and Cultural Research Methods. In conclusion, this strategy can improve learning outcomes by stimulating active student involvement, supporting the introduction of historical and cultural concepts, and encouraging greater participation in the learning process.